Catalogue of Byzantine seals at Dumbarton Oaks and in the Fogg Museum of Art - Nesbitt, John W. 1939-; Oikonomidēs, Nikolaos Antōniu 1934-2000; McGeer, Eric 1955- (Dumbarton Oaks Research Library and Collection, 2020)
Dumbarton Oaks houses the largest collection of Byzantine lead seals in the world, with approximately 17,000 specimens. Volume 7 of the ongoing series of Dumbarton Oaks catalogues presents a distinct part of the collection: 572 anonymous seals bearing sacred images on both sides. The seals, almost all previously unpublished, are fully illustrated and accompanied by a detailed commentary that provides transcriptions of the identifying sigla. This volume represents the first attempt to analyze this group of seals chronologically and typologically.0The depictions of Christ, the Virgin, and a remarkably wide array of saints and narrative scenes offer rich and untapped material for scholars interested in Byzantine piety and culture. Discernible trends within this body of seals help to track the popularity of various saints and the changes in devotional images over time. The variety of these images, enhanced by reference to examples in other collections, will also enable scholars to compare the renderings of holy figures on lead seals to those appearing in other Byzantine religious images.